A self-lubricating liner material and its preparation method and application

By using the combination of WS2@Ti3C2 binary nanocomposite and resin in the fiber fabric self-lubricating composite material, the problem of low fiber surface activity and weak interface bonding is solved, which significantly improves the mechanical and tribological properties of the material and extends the service life.

CN115928420BActive Publication Date: 2025-04-25LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310012013.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-05
Publication Date
2025-04-25
Estimated Expiration
2043-01-05

AI Technical Summary

Technical Problem

The fiber surface of the fiber self-lubricating composite material of fiber fabrics is smooth and has little activity, resulting in weak fiber-resin interface binding, microcracks occur under external stress, increasing wear, and leading to lubrication failure.

Method used

Polyphenylene sulfide fiber and polytetrafluoroethylene fiber are woven, and after desizing, surface cleaning, air plasma treatment and bovine serum protein impregnation, it is finally impregnated, dried and cured in WS2@Ti3C2 binary nanocomposite material and resin solution to form an enhanced self-lubricating pad material.

Benefits of technology

It significantly improves the mechanical properties and tribological properties of self-lubricating pad materials, reduces wear rate and friction coefficient, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115928420B_ABST
    Figure CN115928420B_ABST
Patent Text Reader

Abstract

The present invention provides a self-lubricating gasket material and a preparation method and application thereof, belonging to the technical field of self-lubricating fiber fabric composite materials. The present invention provides a preparation method of a MXene-WS2 nano-functional material reinforced PPS / PTFE self-lubricating gasket material, using PPS fiber with excellent temperature resistance as a reinforcing fiber to weave a PPS / PTFE self-lubricating fiber fabric grey cloth, using air plasma + BSA loading process under mild conditions to improve the fiber-resin interface performance, and using WS2@Ti3C2 binary nanocomposite materials to improve the mechanical properties of the self-lubricating gasket.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of self-lubricating fiber fabric composite materials, and in particular to a self-lubricating liner material and a preparation method and application thereof. Background Art

[0002] Self-lubricating spherical bearings have the advantages of high load-bearing capacity, low friction, wear resistance, long life, and maintenance-free. They are widely used in key and important parts such as aircraft transmission systems, control systems, and power systems, and have a vital impact on aircraft flight safety. The lubrication performance and service life of self-lubricating spherical bearings are largely determined by the self-lubricating liner materials located between the inner and outer rings of the bearings, including metal layered composite materials, polymers and their filled composite materials, and fiber fabric self-lubricating composite materials. Due to the advantages of fiber fabric self-lubricating composite materials such as high load-bearing capacity, wear resistance, strong designability, and good dimensional stability, they are widely used in moving parts such as landing gear, flaperons, rotor systems, and aircraft engines of domestic and foreign aircraft models, and have very good application prospects.

[0003] However, the fiber fabric self-lubricating composite material has the disadvantages of smooth fiber surface and low activity, which leads to weak interface bonding between it and the resin matrix. Under the action of external stress, micro cracks are generated at the fiber-resin interface, resulting in increased wear and ultimately leading to lubrication failure. Although the reinforcement of micro-nano materials can improve the mechanical properties and tribological properties of self-lubricating fiber fabric composite materials, the improvement of the tribological properties of self-lubricating composite materials is limited, and the wear debris generated during the friction process may aggravate the wear of the liner. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a self-lubricating gasket material and a preparation method and application thereof. The self-lubricating gasket material prepared by the present invention has excellent mechanical properties and tribological properties.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a self-lubricating gasket material, comprising the following steps:

[0007] The polyphenylene sulfide fiber is used as the weft yarn and the polytetrafluoroethylene fiber is used as the warp yarn to weave to obtain the fabric;

[0008] The fabric is sequentially subjected to desizing treatment and surface cleaning to obtain a PPS / PTFE fiber fabric grey cloth;

[0009] The PPS / PTFE fiber fabric grey cloth is treated with air plasma, and then immersed in a bovine serum albumin aqueous solution to obtain a BSA-PPS / PTFE fabric;

[0010] mixing MXene nanosheets, a sulfur source, a tungsten source, and water to obtain a mixed solution;

[0011] The mixed solution is subjected to a hydrothermal reaction to obtain a WS2@Ti3C2 binary nanocomposite material;

[0012] Mixing the WS2@Ti3C2 binary nanocomposite material, a resin and a solvent to obtain a resin solution;

[0013] The BSA-PPS / PTFE fabric is immersed in the resin solution and then dried and cured in sequence to obtain the self-lubricating gasket material.

[0014] Preferably, the power of the air plasma treatment is 30 to 200 W, and the time is 3 to 60 minutes.

[0015] Preferably, the mass concentration of MXene nanosheets in the mixed solution is 0.2-6 mg / mL, the mass concentration of the sulfur source is 0.02-0.3 g / mL, the mass concentration of the tungsten source is 0.01-0.3 g / mL, the sulfur source is C2H5NS, and the tungsten source is WCl6.

[0016] Preferably, the temperature of the hydrothermal reaction is 270-300° C., and the time is 24-36 hours.

[0017] Preferably, the mass fraction of the WS2@Ti3C2 binary nanocomposite material in the resin solution is 1%.

[0018] Preferably, the mass volume ratio of the resin to the solvent in the resin solution is 0.05 to 1.5 g / mL.

[0019] Preferably, the resin includes one or more of phenolic resin, polyimide resin, epoxy resin and polyamideimide.

[0020] Preferably, the curing temperature is 150-200° C. and the curing time is 1.5-3 hours.

[0021] The present invention also provides a self-lubricating gasket material obtained by the preparation method described in the above technical solution.

[0022] The present invention also provides the application of the self-lubricating liner material described in the above technical solution in the field of self-lubricating spherical bearings.

[0023] The invention provides a preparation method of a self-lubricating gasket material, comprising the following steps: using polyphenylene sulfide fiber as weft yarn and polytetrafluoroethylene fiber as warp yarn to weave a fabric; sequentially performing desizing treatment and surface cleaning on the fabric to obtain a PPS / PTFE fiber fabric grey cloth; performing air plasma treatment on the PPS / PTFE fiber fabric grey cloth, and then immersing the grey cloth in a bovine serum albumin aqueous solution to obtain a BSA-PPS / PTFE fabric; mixing MXene nanosheets, a sulfur source, a tungsten source and water to obtain a mixed solution; performing a hydrothermal reaction on the mixed solution to obtain a WS2@Ti3C2 binary nanocomposite material; mixing the WS2@Ti3C2 binary nanocomposite material, a resin and a solvent to obtain a resin solution; immersing the BSA-PPS / PTFE fabric in the resin solution, and then sequentially drying and curing to obtain the self-lubricating gasket material.

[0024] The present invention provides a preparation method of a MXene-WS2 nano-functional material reinforced PPS / PTFE self-lubricating gasket material, wherein PPS fiber with excellent temperature resistance is used as reinforcing fiber to weave a PPS / PTFE self-lubricating fiber fabric grey cloth, and an air plasma + BSA loading process is used under mild conditions to improve the fiber-resin interface performance, and at the same time, the WS2@Ti3C2 binary nano-composite material is used to improve the mechanical properties and tribological properties of the self-lubricating gasket, thereby achieving the improvement of the mechanical properties and tribological properties of the fiber fabric self-lubricating gasket material.

[0025] The tensile strength and peel strength of the prepared self-lubricating fiber fabric composites were systematically evaluated using a universal materials testing machine. It can be seen that pure PPS / PTFE self-lubricating fiber fabric composites exhibit the lowest tensile strength and peel strength, interface modification (BSA adsorbed on the fiber surface) and the addition of functional reinforcing materials can improve the tensile strength and peel strength of the fiber fabric composites, and the PPS / PTFE-BSA fiber fabric composites reinforced with WS2@Ti3C2 binary nanocomposite materials exhibit the most excellent mechanical properties; the friction coefficient and wear amount of the self-lubricating pad were measured using a pin-disc friction and wear tester (dual diameter 2mm) at room temperature, 35MPa dynamic load, 0.4m / s working conditions (test time 120min). It can be seen that BSA interface modification, WS2, Ti3C2, and WS2@Ti3C2 can all reduce the wear rate and friction coefficient of the PPS / PTFE self-lubricating fiber fabric composites, but the WS2@Ti3C2 reinforced PPS / PTFE-BSA fiber fabric composite has the smallest wear rate and friction coefficient. The above results show that the method of the present invention has a very obvious promoting effect on improving the mechanical properties and tribological properties of the PPS / PTFE fiber fabric self-lubricating composite material.

[0026] The present invention also provides a self-lubricating fiber fabric composite material prepared by the preparation method described in the above technical scheme, the fabric surface is flawless and smooth, the MXene-WS2 nano-functional material is evenly distributed, and no aggregation or agglomeration is observed. The self-lubricating pad bonded to the surface of the metal substrate is wrinkle-free, bubble-free, and smooth. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 1 is a bar graph of the tensile strength and peel strength of the self-lubricating fiber fabric composite material obtained in Examples 1 to 6, wherein (a) is the tensile strength and (b) is the peel strength;

[0028] Figure 2 It is a bar graph of the wear rate and friction coefficient of the self-lubricating fiber fabric composite material obtained in Examples 1 to 6, wherein (a) is the wear rate and (b) is the friction coefficient. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing a self-lubricating gasket material, comprising the following steps:

[0030] Polyphenylene sulfide (PPS) fiber is used as weft yarn and polytetrafluoroethylene (PTFE) fiber is used as warp yarn to weave to obtain a fabric;

[0031] The fabric is sequentially subjected to desizing treatment and surface cleaning to obtain a PPS / PTFE fiber fabric grey cloth;

[0032] The PPS / PTFE fiber fabric grey cloth is treated with air plasma, and then immersed in a bovine serum albumin aqueous solution to obtain a BSA-PPS / PTFE fabric;

[0033] mixing MXene nanosheets, a sulfur source, a tungsten source, and water to obtain a mixed solution;

[0034] The mixed solution is subjected to a hydrothermal reaction to obtain a WS2@Ti3C2 binary nanocomposite material;

[0035] Mixing the WS2@Ti3C2 binary nanocomposite material, a resin and a solvent to obtain a resin solution;

[0036] The BSA-PPS / PTFE fabric is immersed in the resin solution and then dried and cured in sequence to obtain the self-lubricating gasket material.

[0037] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.

[0038] The invention uses polyphenylene sulfide (PPS) fiber as weft yarn and polytetrafluoroethylene (PTFE) fiber as warp yarn to weave and obtain fabric.

[0039] In the present invention, the PPS fiber has high temperature resistance, and the PTFE fiber has lubricating properties.

[0040] In the present invention, the weaving is preferably carried out in a loom. The present invention has no special limitation on the specific manner of the weaving, and a manner well known to those skilled in the art may be adopted.

[0041] In the present invention, the fabric is preferably plain weave, twill weave, satin weave or one of the evolved structures of the above three basic weave structures.

[0042] After obtaining the fabric, the invention sequentially performs desizing treatment and surface cleaning on the fabric to obtain PPS / PTFE fiber fabric grey cloth.

[0043] The present invention has no particular limitation on the specific methods of the desizing treatment and surface cleaning, and methods well known to those skilled in the art may be used.

[0044] In the present invention, the surface cleaning is used to remove the oil on the fiber surface.

[0045] In the present invention, the PPS / PTFE fiber fabric grey cloth preferably has a warp density of 200 to 380 strands / 10 cm, and a weft density of 200 to 350 strands / 10 cm.

[0046] After obtaining the PPS / PTFE fiber fabric grey cloth, the present invention performs air plasma treatment on the PPS / PTFE fiber fabric grey cloth and then immerses the cloth in a bovine serum albumin (BSA) aqueous solution to obtain a BSA-PPS / PTFE fabric.

[0047] In the present invention, the power of the air plasma treatment is preferably 30 to 200 W, more preferably 100 to 150 W, and the time is preferably 3 to 60 min, more preferably 10 to 30 min. The air plasma treatment can introduce oxygen-containing groups into the fiber surface, thereby significantly improving the surface energy and roughness of the fiber, improving the interfacial adhesion of the fiber, and the plasma can introduce oxygen-containing groups, such as -OH and -COOH, into the fiber surface, thereby strengthening the connection between the BSA molecule and the fiber surface by forming chemical bonds or hydrogen bonds.

[0048] In the present invention, the concentration of the bovine serum albumin aqueous solution is preferably 0.1 to 6 wt %, more preferably 1.5 to 3 wt %, and the immersion time is preferably 5 to 60 min, more preferably 10 to 30 min.

[0049] In the present invention, the air plasma treatment and immersion in a bovine serum albumin (BSA) aqueous solution act to activate the fiber surface.

[0050] The present invention mixes MXene (Ti3C2) nanosheets, a sulfur source, a tungsten source and water to obtain a mixed solution.

[0051] The present invention has no special limitation on the source of the MXene (Ti3C2) nanosheets, and the MXene (Ti3C2) nanosheets can be prepared by methods well known to those skilled in the art, such as etching Ti3C2 using an HCl+LiF system to prepare the MXene (Ti3C2) nanosheets.

[0052] In the present invention, the mass concentration of MXene nanosheets in the mixed solution is preferably 0.2-6 mg / mL, the mass concentration of the sulfur source is preferably 0.02-0.3 g / mL, the mass concentration of the tungsten source is preferably 0.01-0.3 g / mL, the sulfur source is preferably C2H5NS, and the tungsten source is preferably WCl6.

[0053] The present invention has no particular limitation on the specific manner of mixing. Specifically, the Ti3C2 is added to deionized water for ultrasonic dispersion, the C2H5NS and tungsten source are dispersed in deionized water by magnetic stirring, and then poured into the obtained Ti3C2 solution and vigorously stirred for 1 to 2 hours.

[0054] After obtaining the mixed solution, the present invention performs a hydrothermal reaction on the mixed solution to obtain a WS2@Ti3C2 binary nanocomposite material.

[0055] In the present invention, the temperature of the hydrothermal reaction is preferably 270-300° C., the time is preferably 24-36 hours, and the hydrothermal reaction is preferably carried out in a muffle furnace.

[0056] After the hydrothermal reaction is completed, the present invention preferably cools the obtained hydrothermal product naturally to room temperature and then separates the solid and liquid, washes the obtained soil with deionized water and freeze-dries it to obtain the WS2@Ti3C2 binary nanocomposite material.

[0057] The present invention has no particular limitation on the specific method of washing with deionized water and freeze-drying, and any method well known to those skilled in the art may be used.

[0058] After obtaining the WS2@Ti3C2 binary nanocomposite material, the present invention mixes the WS2@Ti3C2 binary nanocomposite material, a resin and a solvent to obtain a resin solution.

[0059] In the present invention, the mass fraction of the WS2@Ti3C2 binary nanocomposite material in the resin solution is preferably 1%.

[0060] In the present invention, the mass volume ratio of the resin to the solvent in the resin solution is preferably 0.05 to 1.5 g / mL.

[0061] In the present invention, the resin preferably includes one or more of phenolic resin, polyimide resin, epoxy resin and polyamideimide.

[0062] After obtaining the BSA-PPS / PTFE fabric and the resin solution, the present invention immerses the BSA-PPS / PTFE fabric in the resin solution and then sequentially performs drying and curing to obtain the self-lubricating gasket material.

[0063] The present invention has no particular limitation on the number of times of the impregnation, and preferably the impregnation is performed until the mass fraction of the BSA-PPS / PTFE fabric in the impregnated product is 70-80%. In the present invention, each impregnation preferably includes drying, and the present invention has no particular limitation on the specific drying method, and a method well known to those skilled in the art can be used.

[0064] In the present invention, the curing temperature is preferably 150-200° C., more preferably 160-184° C., and the curing time is preferably 1.5-3 h, more preferably 2 h.

[0065] In the present invention, the curing is preferably completed on the surface of the metal part.

[0066] In the present invention, the WS2@Ti3C2 binary nanocomposite material exists in the self-lubricating gasket material in the form of solid nanoparticles.

[0067] The present invention also provides a self-lubricating gasket material obtained by the preparation method described in the above technical solution.

[0068] The present invention also provides the application of the self-lubricating liner material described in the above technical solution in the field of self-lubricating spherical bearings.

[0069] In order to further illustrate the present invention, the self-lubricating gasket material provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the protection scope of the present invention.

[0070] Example 1

[0071] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE fiber fabric, which is desized and cleaned with fiber surface oil and then dried for use;

[0072] (2) The unactivated PPS / PTFE fiber fabric was repeatedly immersed in a phenolic resin solution until the mass fraction of the fabric reached 75% to obtain an uncured PPS / PTFE fiber fabric, which was bonded to a friction and wear and peeling test piece using a phenolic resin adhesive and cured at 184°C for 2h to obtain a self-lubricating fiber fabric composite material test piece;

[0073] (3) Under room temperature, the peel strength and friction and wear performance tests were carried out. The tensile strength of the PPS / PTFE fiber fabric composite material without any treatment was 112.39 MPa, the peel strength was 0.54 N / mm, the friction coefficient was 0.058, and the wear rate was 4.47×10 -14 m 3 / N·m.

[0074] Example 2

[0075] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE fiber fabric, which is desized and cleaned with fiber surface oil and then dried for use;

[0076] (2) The unactivated PPS / PTFE fiber fabric was repeatedly immersed in a phenolic resin solution (the mass fraction of WS2 in the phenolic resin solution was 1wt%) until the mass fraction of the fabric reached 75% to obtain an unsolidified PPS / PTFE fiber fabric, which was bonded to a friction and wear and peeling test piece using a phenolic resin adhesive and cured at 184°C for 2h to obtain a self-lubricating fiber fabric composite material test piece;

[0077] (3) Under room temperature, the peel strength and friction and wear performance tests were carried out. The tensile strength of the PPS / PTFE fiber fabric composite material without any treatment was 134.57 MPa, the peel strength was 0.446 N / mm, the friction coefficient was 0.056, and the wear rate was 3.69×10 -14 m 3 / N·m.

[0078] Example 3

[0079] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE fiber fabric, which is desized and cleaned with fiber surface oil and then dried for use;

[0080] (2) The unactivated PPS / PTFE fiber fabric was repeatedly immersed in a phenolic resin solution (the mass fraction of Ti3C2 in the phenolic resin solution was 1wt%) until the mass fraction of the fabric reached 75% to obtain an unsolidified PPS / PTFE fiber fabric, which was bonded to a friction and wear and peeling test piece using a phenolic resin adhesive and cured at 184°C for 2h to obtain a self-lubricating fiber fabric composite material test piece;

[0081] (3) Under room temperature, the peel strength and friction and wear performance tests were carried out. The tensile strength of the PPS / PTFE fiber fabric composite material without any treatment was 137.16 MPa, the peel strength was 0.462 N / mm, the friction coefficient was 0.055, and the wear rate was 3.71×10 -14 m 3 / N·m.

[0082] Example 4

[0083] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE fiber fabric, which is desized and cleaned with fiber surface oil and then dried for use;

[0084] (2) Surface activation of the fiber fabric was performed using air plasma (100 W, 10 min), and then the fabric was immersed in a dilute solution of BSA (mass concentration 1.5 wt%) and dried after 20 min;

[0085] (3) The activated PPS / PTFE-BSA fiber fabric was repeatedly immersed in a phenolic resin solution until the mass fraction of the fabric reached 75% to obtain an unsolidified PPS / PTFE fiber fabric, which was bonded to a friction and wear and peeling test piece using a phenolic resin adhesive and cured at 184°C for 2h to obtain a self-lubricating fiber fabric composite material test piece;

[0086] (4) Under room temperature, the peel strength and friction and wear performance tests were carried out. The tensile strength of the PPS / PTFE fiber fabric composite material without any treatment was 136.75 MPa, the peel strength was 0.86 N / mm, the friction coefficient was 0.053, and the wear rate was 2.93×10 -14 m 3 / N·m.

[0087] Example 5

[0088] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE fiber fabric, which is desized and cleaned with fiber surface oil and then dried for use;

[0089] (2) Take 35mL 9M HCl and 1g LiF into a plastic bottle, seal it and stir for 10min. Then slowly add 1g Ti3AlC2 into the above mixture and etch it for 36h under magnetic stirring at 40℃. After etching, the crude product is centrifuged with deionized water and ethanol until the pH of the supernatant is 6.5. Then, place the Ti3C2 solution in an ice-water bath under argon atmosphere, sonicate for 1h and centrifuge for 1h to obtain a uniform dark green suspension. Finally, freeze-dry the suspension for 36h for further use;

[0090] (3) 90 mg Ti3C2 was added to 30 mL deionized water for ultrasonic dispersion, and then 1.75 g C2H5NS and 0.9 g WCl6 were dispersed in 20 mL deionized water by magnetic stirring and poured into the above Ti3C2 solution and stirred vigorously for 1.5 h. Next, the mixed solution was transferred to a 100 mL reactor and placed in a muffle furnace at 270 ° C for 24 h to obtain WS2@Ti3C2 binary nanocomposite materials. After cooling to room temperature, the product was centrifuged, washed with deionized water and freeze-dried.

[0091] (4) The unactivated PPS / PTFE fiber fabric was repeatedly immersed in a phenolic resin solution containing WS2@Ti3C2 binary nanocomposite material (the mass fraction of WS2@Ti3C2 was 1wt%) until the mass fraction of the fabric reached 75% to obtain an unsolidified PPS / PTFE fiber fabric, which was bonded to a friction and wear and peeling test piece using a phenolic resin adhesive and cured at 184°C for 2h to obtain a self-lubricating fiber fabric composite material test piece;

[0092] (5) At room temperature, the peel strength and friction and wear performance tests were carried out. The tensile strength of the WS2@Ti3C2 reinforced PPS / PTFE-BSA fiber fabric composite material was 147.2 MPa, the peel strength was 0.70 N / mm, the friction coefficient was 0.0532, and the wear rate was 2.52×10 -14 m 3 / N·m.

[0093] Example 6

[0094] (1) PPS fiber and PTFE fiber were used to weave PPS / PTFE fiber fabric, which was desized and cleaned with a fiber surface oil agent and then dried for use. The PPS / PTFE fiber fabric was surface activated by air plasma (100 W, 10 min). The treated fabric was immersed in a BSA dilute solution with a mass concentration of 1.5 wt%, and then taken out and dried after 20 min.

[0095] (2) Take 35mL 9M HCl and 1g LiF into a plastic bottle, seal it and stir for 10min. Then slowly add 1g Ti3AlC2 into the above mixture and etch it for 36h under magnetic stirring at 40℃. After etching, the crude product is centrifuged with deionized water and ethanol until the pH of the supernatant is 6.5. Then, place the Ti3C2 solution in an ice-water bath under argon atmosphere, sonicate for 1h and centrifuge for 1h to obtain a uniform dark green suspension. Finally, freeze-dry the suspension for 36h for further use;

[0096] (3) 90 mg Ti3C2 was added to 30 mL deionized water for ultrasonic dispersion, and then 1.75 g C2H5NS and 0.9 g WCl6 were dispersed in 20 mL deionized water by magnetic stirring and poured into the above Ti3C2 solution and stirred vigorously for 1.5 h. Next, the mixed solution was transferred to a 100 mL reactor and placed in a muffle furnace at 270 ° C for 24 h to obtain WS2@Ti3C2 binary nanocomposite materials. After cooling to room temperature, the product was centrifuged, washed with deionized water and freeze-dried.

[0097] (4) The BSA-activated PPS / PTFE fiber fabric was repeatedly immersed in a phenolic resin solution containing WS2@Ti3C2 binary nanocomposite material (the mass fraction of WS2@Ti3C2 was 0.5wt%) until the mass fraction of the fabric reached 75% to obtain an unsolidified PPS / PTFE fiber fabric, which was bonded to a friction and wear and peeling test piece using a phenolic resin adhesive and cured at 184°C for 2h to obtain a self-lubricating fiber fabric composite material test piece;

[0098] (5) At room temperature, the peel strength and friction and wear performance tests were carried out. The tensile strength of the WS2@Ti3C2 reinforced PPS / PTFE-BSA fiber fabric composite material was 140.5 MPa, the peel strength was 0.778 N / mm, the friction coefficient was 0.0585, and the wear rate was 2.07×10 -14 m 3 / N·m.

[0099] Example 7

[0100] (1) PPS fiber and PTFE fiber were used to weave PPS / PTFE fiber fabric, which was desized and cleaned with a fiber surface oil agent and then dried for use. The PPS / PTFE fiber fabric was surface activated by air plasma (100 W, 10 min). The treated fabric was immersed in a BSA dilute solution with a mass concentration of 1.5 wt%, and then taken out and dried after 20 min.

[0101] (2) Take 35mL 9M HCl and 1g LiF into a plastic bottle, seal it and stir for 10min. Then slowly add 1g Ti3AlC2 into the above mixture and etch it for 36h under magnetic stirring at 40℃. After etching, the crude product is centrifuged with deionized water and ethanol until the pH of the supernatant is 6.5. Then, place the Ti3C2 solution in an ice-water bath under argon atmosphere, sonicate for 1h and centrifuge for 1h to obtain a uniform dark green suspension. Finally, freeze-dry the suspension for 36h for further use;

[0102] (3) 90 mg Ti3C2 was added to 30 mL deionized water for ultrasonic dispersion, and then 1.75 g C2H5NS and 0.9 g WCl6 were dispersed in 20 mL deionized water by magnetic stirring and poured into the above Ti3C2 solution and stirred vigorously for 1.5 h. Next, the mixed solution was transferred to a 100 mL reactor and placed in a muffle furnace at 270 ° C for 24 h to obtain WS2@Ti3C2 binary nanocomposite materials. After cooling to room temperature, the product was centrifuged, washed with deionized water and freeze-dried.

[0103] (4) The BSA-activated PPS / PTFE fiber fabric was repeatedly immersed in a phenolic resin solution containing WS2@Ti3C2 binary nanocomposite material (the mass fraction of WS2@Ti3C2 was 1wt%) until the mass fraction of the fabric reached 75% to obtain an unsolidified PPS / PTFE fiber fabric, which was bonded to a friction and wear and peeling test piece using a phenolic resin adhesive and cured at 184°C for 2h to obtain a self-lubricating fiber fabric composite material test piece;

[0104] (5) At room temperature, the peel strength and friction and wear performance tests were carried out. The tensile strength of the WS2@Ti3C2 reinforced PPS / PTFE-BSA fiber fabric composite material was 152.76 MPa, the peel strength was 0.91 N / mm, the friction coefficient was 0.0537, and the wear rate was 1.81×10 -14 m 3 / N·m.

[0105] Example 8

[0106] (1) PPS fiber and PTFE fiber were used to weave PPS / PTFE fiber fabric, which was desized and cleaned with a fiber surface oil agent and then dried for use. The PPS / PTFE fiber fabric was surface activated by air plasma (100 W, 10 min). The treated fabric was immersed in a BSA dilute solution with a mass concentration of 1.5 wt%, and then taken out and dried after 20 min.

[0107] (2) Take 35mL 9M HCl and 1g LiF into a plastic bottle, seal it and stir for 10min. Then slowly add 1g Ti3AlC2 into the above mixture and etch it for 36h under magnetic stirring at 40℃. After etching, the crude product is centrifuged with deionized water and ethanol until the pH of the supernatant is 6.5. Then, place the Ti3C2 solution in an ice-water bath under argon atmosphere, sonicate for 1h and centrifuge for 1h to obtain a uniform dark green suspension. Finally, freeze-dry the suspension for 36h for further use;

[0108] (3) 90 mg Ti3C2 was added to 30 mL deionized water for ultrasonic dispersion, and then 1.75 g C2H5NS and 0.9 g WCl6 were dispersed in 20 mL deionized water by magnetic stirring and poured into the above Ti3C2 solution and stirred vigorously for 1.5 h. Next, the mixed solution was transferred to a 100 mL reactor and placed in a muffle furnace at 270 ° C for 24 h to obtain WS2@Ti3C2 binary nanocomposite materials. After cooling to room temperature, the product was centrifuged, washed with deionized water and freeze-dried.

[0109] (4) The BSA-activated PPS / PTFE fiber fabric was repeatedly immersed in a phenolic resin solution containing WS2@Ti3C2 binary nanocomposite material (the mass fraction of WS2@Ti3C2 was 1.5wt%) until the mass fraction of the fabric reached 75% to obtain an unsolidified PPS / PTFE fiber fabric, which was bonded to a friction and wear and peeling test piece using a phenolic resin adhesive and cured at 184°C for 2h to obtain a self-lubricating fiber fabric composite material test piece;

[0110] (5) At room temperature, the peel strength and friction and wear performance tests were carried out. The tensile strength of the WS2@Ti3C2 reinforced PPS / PTFE-BSA fiber fabric composite material was 135.06 MPa, the peel strength was 0.799 N / mm, the friction coefficient was 0.0582, and the wear rate was 2.11×10 -14 m 3 / N·m.

[0111] Figure 1 1 is a bar graph of the tensile strength and peel strength of the self-lubricating fiber fabric composite material obtained in Examples 1 to 8, wherein (a) is the tensile strength and (b) is the peel strength; Figure 2 The wear rate and friction coefficient bar graphs of the self-lubricating fiber fabric composite materials obtained in Examples 1 to 8, wherein (a) is the wear rate and (b) is the friction coefficient. Figures 1-2 It can be seen that BSA interface modification, WS2, Ti3C2, and WS2@Ti3C2 can all improve the tribological properties of PPS / PTFE self-lubricating fiber fabric composites, but WS2@Ti3C2 reinforced PPS / PTFE-BSA fiber fabric composites have the best tribological and mechanical properties. The above results show that the method described in the present invention has a very obvious promoting effect on improving the mechanical properties and tribological properties of PPS / PTFE fiber fabric self-lubricating composites.

[0112] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a self-lubricating gasket material, characterized in that: The following steps are involved: The polyphenylene sulfide fiber is used as the weft yarn and the polytetrafluoroethylene fiber is used as the warp yarn to weave to obtain the fabric; The fabric is sequentially subjected to desizing treatment and surface cleaning to obtain a PPS / PTFE fiber fabric grey cloth; The PPS / PTFE fiber fabric grey cloth is treated with air plasma, and then immersed in a bovine serum albumin aqueous solution to obtain a BSA-PPS / PTFE fabric; mixing MXene nanosheets, a sulfur source, a tungsten source, and water to obtain a mixed solution; The mixed solution is subjected to a hydrothermal reaction to obtain a WS2@Ti3C2 binary nanocomposite material; Mixing the WS2@Ti3C2 binary nanocomposite material, a resin and a solvent to obtain a resin solution; The BSA-PPS / PTFE fabric is immersed in the resin solution and then dried and cured in sequence to obtain the self-lubricating gasket material.

2. The preparation method according to claim 1, characterized in that: The power of the air plasma treatment is 30 to 200 W, and the time is 3 to 60 minutes.

3. The preparation method according to claim 1, characterized in that: The mass concentration of MXene nanosheets in the mixed solution is 0.2-6 mg / mL, the mass concentration of the sulfur source is 0.02-0.3 g / mL, and the mass concentration of the tungsten source is 0.01-0.3 g / mL. The sulfur source is C2H5NS, and the tungsten source is WCl6.

4. The preparation method according to claim 1 or 3, characterized in that: The temperature of the hydrothermal reaction is 270-300° C. and the time is 24-36 hours.

5. The preparation method according to claim 1, characterized in that: The mass fraction of the WS2@Ti3C2 binary nanocomposite material in the resin solution is 1%.

6. The preparation method according to claim 1 or 5, characterized in that: The mass volume ratio of the resin to the solvent in the resin solution is 0.05 to 1.5 g / mL.

7. The preparation method according to claim 1 or 5, characterized in that: The resin includes one or more of phenolic resin, polyimide resin, epoxy resin and polyamideimide.

8. The preparation method according to claim 1, characterized in that: The curing temperature is 150-200° C. and the curing time is 1.5-3 hours.

9. The self-lubricating gasket material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the self-lubricating gasket material according to claim 9 in the field of self-lubricating spherical plain bearings.

Citation Information

Patent Citations

  • Polytetrafluoroethylene self-reinforced composite material and preparation method thereof

    CN102206391A

  • Self-lubricating fabric and application thereof

    CN111139653A